Achievement Oriented Culture : The Effective Performance Assessment System for Organization - Moerkardjono, Sukma Rani (Noetic Psychology, 2014)
AbstractPerformance assessment plays important roles in company, both its employees and organization.ÃÂ ÃÂ  Organization implementingÃÂ ÃÂ ÃÂ  Achivement Oriented Culture will develop clear performance assessment that ones performance effectivity will be clearly showed by mean of performance assessment system. The effective assessment system must be able to measure the level of individual, organizational, and motivationalÃÂ  performances. Based on the fact in national banking organization implementingÃÂ  performance assesment systems of result based and competency based combinations. The doubt of performance assesment system implementation is due to reward inconsistency so it will be affecting to the result of performance assessment and other factors such as incentive, employees motivation, and companys profit.ÃÂ  This research is a case study in nasional banking organization. The method of data collection is done by deep interview and management data showing reward inconsistency on performane assessment.The study is to find the causes of ratescute for the result of employee performance assessment. The recomendation is the improvement of performance assessment system. Keywords : achivement oriented culture, result-based performance assessment competency-based performance assessment, performance appraisal system